BAHASA PERLAWANAN DAN POLITIK TUBUH DALAM TEORI DRAMA PASCA-KOLONIAL HELEN GILBERT DAN JOANNE TOMPKINS - Khurosan, Herpin Nopiandi; Yuliatin, Riyana Rizki (Universitas Hamzanwadi, 2020)
This paper is a review and preparation of concepts, ideas and theoris of post-colonial drama in Helen Gilbert andTompkins?s sense. I use ?Post-Colonial Drama: Theory, Practice, Politics? as a main source of their ideas about post-colonial Drama. I limited this paper in theories of canonical counter-discourse, the language of resistance, and body politics in post-colonial context. The result of this reconstruction to their theories is developed to become theoretical and methodological framework which can be used to analyse post-colonial drama in later researches.